Buffer or Backfire? Effects of Corporate Social Responsibility Activities in Organizational Crises (Journal of International Crisis and Risk Communication Research, 2022)
Corporate social responsibility (CSR) activities can help an organization to build a favorable reputation; such activities can thereby serve as a buffer in times of crisis. However, research also suggests that these activities can backfire and reinforce the reputational damage caused by a crisis because they can lead to elevated expectations among the stakeholders. Drawing on prior research on buffering and backfire effects, this study examines the possible moderating effects of crisis type and severity. Two experiments show that CSR activities positively affect the perceptions of a company’s affective image. In times of crisis, this image boost indeed serves as a buffer in a victim crisis and in a preventable crisis (contrary to our expectations). However, in the case of a very severe crisis, CSR activities can also backfire and a company that engages in CSR activities matching the field of the corporate crisis is perceived morenegatively.